Impact strength of Carbon Reinforced Epoxy Composite at different temperatures - Mridha, Shahjahan; Lenda, T.A. (2011)
Charpy impact tests were conducted on carbon reinforced epoxy composites fabricated by hand lay-up method using 0.47, 0.56 and 0.66 carbon fiber volume fractions; tests were conducted at temperatures between -60oC to 60oC. The impact strength was found, in general, to increase when the samples were fractured at temperatures above 0oC and the impact strength decreased with the increase of fiber content. The impact energy absorption was highest of 270 KJm-2 with 47 vol% fiber when fractured at +60oC and it reduced to 130 KJm-2 at -60oC. With decreasing the fracture temperature and increasing the fiber content the impact strength reduced significantly. The reduction of impact energy was from 235 KJm-2 to 107 KJm-2 for 56 vol% fiber and from 196 KJm-2 to 90 KJm-2 for 66 vol% fiber when fractured at +60oC and -60oC, respectively. Failure occurred mostly by fiber delamination; fiber splitting and matrix cracking were also present. Delamination was more in specimens tested at -60oC while fiber splitting and matrix cracking were more when fractured at +60oC.